Dataset relating to "Permeability measurements for the Investigation of a practical approach to the measurement of magnetic permeability of ferrofluids" - Lakshminarayanan, Venkatasubramanian; Qin, Qing; Geng, Jiaxin; Luo, Zhenhua (Cranfield University, 2024)
Ferrofluids are colloids of magnetic particles in a fluid. Ferrofluids have wide range of application in engineering and medicine. Their relative magnetic permeability is one of the important parameters that needs to be measured. This dataset contains the measurements observed in the process of using an existing technique to measure magnetic permeability with a solenoid and LCR meter to identify experimental factors relevant to the accuracy of measurement.
Keywords: ferrofluid; magnetic; permeability; measurement